2002
DOI: 10.1074/jbc.m208669200
|View full text |Cite
|
Sign up to set email alerts
|

The Active Principle of Garlic at Atomic Resolution

Abstract: Despite the fact that many cultures around the world value and utilize garlic as a fundamental component of their cuisine as well as of their medicine cabinets, relatively little is known about the plant's protein configuration that is responsible for the specific properties of garlic. Here, we report the three-dimensional structure of the garlic enzyme alliinase at 1.5 Å resolution. Alliinase constitutes the major protein component in garlic bulbs, and it is able to cleave carbon-sulfur bonds. The active enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 28 publications
2
70
0
Order By: Relevance
“…S3). Further, structural studies show that the garlic alliinase is very similar to aminotransferases (Kuettner et al, 2002). Together with the earlier studies of Stepanova et al (2008) and Tao et al (2008), our analysis indicates that TIR2 is a Trp aminotransferase that synthesizes IPA from Trp (Fig.…”
Section: Tir2 Is Required For Diverse Auxin-dependent Processes In Thsupporting
confidence: 83%
See 2 more Smart Citations
“…S3). Further, structural studies show that the garlic alliinase is very similar to aminotransferases (Kuettner et al, 2002). Together with the earlier studies of Stepanova et al (2008) and Tao et al (2008), our analysis indicates that TIR2 is a Trp aminotransferase that synthesizes IPA from Trp (Fig.…”
Section: Tir2 Is Required For Diverse Auxin-dependent Processes In Thsupporting
confidence: 83%
“…S1B). The function of alliinase has previously been characterized in garlic and onion (Allium cepa; Kuettner et al, 2002). This enzyme catalyzes the conversion of a specific nonprotein sulfur-containing amino acid called alliin to allicin, a compound with antibiotic activity.…”
Section: Tir2 Is Required For Diverse Auxin-dependent Processes In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous amino-acid sequence analysis revealed 10 cysteine residues per alliinase subunit, 2 and X-ray crystal structure showed that six of these cysteine residues form three adjacent disulfide bridges at the N-terminal part of the alliinase subunit. 4,6 In the present study, we examined the configuration and reactivity of the remaining four cysteine residues and demonstrated that two free thiols are located far from the active site of the enzyme, and their modification does not affect the enzyme's structure and activity. Cys368 and Cys376 form a SAS bridge located close to C-terminus and has a role in maintaining both the rigidity of the catalytic domain and the substrate-cofactor relative orientation.…”
Section: Introductionmentioning
confidence: 80%
“…[3][4][5][6] The enzyme is a homodimeric glycoprotein belonging to the fold-type I family of PLP-dependent enzymes. Allicin, a product of the enzymatic reaction of alliinase with alliin, is the well-characterized, biologically active compound of garlic.…”
Section: Introductionmentioning
confidence: 99%